Inter-Vehicle-Communications - Based on Ad Hoc Networking Principles : The FleetNet Project - Franz, WalterHartenstein, HannesMauve, Martin [Hrsg.] (KIT Scientific Publishing, 2005)
Vehicular Ad Hoc Networks (VANETs) represent an emerging topic in wireless communication and networking. VANETs are currently receiving a lot of attention due to their promise of considerably increasing safety and comfort while being on the road. High mobility, adverse channel conditions, and market introduction are some of the key challenges one has to deal with when designing these spontaneous networks. Inter-Vehicle-Communications Based on Ad Hoc Networking Principles covers results and achievements of the FleetNet project, a project devoted to the design of a vehicular ad hoc network.